2006
DOI: 10.1002/biot.200600029
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐guided consensus approach to create a more thermostable penicillin G acylase

Abstract: The thermostabilization of penicillin G acylase (PGA) is a difficult problem due to the large size of the protein and its complex maturation process. We developed a data-driven protein design method that requires fewer homologous sequences than the traditional consensus approach and utilizes structural information to limit the number of variants created. Approximately 50% of our 21 single-point mutants were found experimentally to be more thermostable than the wild-type PGA, two had almost threefold longer hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…Consensus mutations comprise the most easily identifiable potential of stabilizing mutations that can boost protein evolvability (25). As less than half of the predicted consensus mutations actually have a stabilizing effect (24,36), and different mutations become compensatory at different evolutionary stages (as seen in R1-R2 versus R7 and later), spiking these mutations into libraries is a more effective strategy than the use of a prestabilized starting point (20).…”
Section: Discussionmentioning
confidence: 99%
“…Consensus mutations comprise the most easily identifiable potential of stabilizing mutations that can boost protein evolvability (25). As less than half of the predicted consensus mutations actually have a stabilizing effect (24,36), and different mutations become compensatory at different evolutionary stages (as seen in R1-R2 versus R7 and later), spiking these mutations into libraries is a more effective strategy than the use of a prestabilized starting point (20).…”
Section: Discussionmentioning
confidence: 99%
“…The high functionality of the consensus library can be attributed to the choice of specific point mutations and the application of eliminating criteria to reduce destructive mutations. It was previously shown that the datadriven consensus approach is useful in creating mutant libraries of high functionality, which enables the screening effort to be minimized (39,42,47,61). Low functionality of a random mutagenesis library may be a result of a high mutation rate and multiple alterations that can lead to destabilization and unfolding of the enzyme (36,66).…”
Section: Figmentioning
confidence: 99%
“…Protein engineering by introduction of ancestral/consensus residues to the enzyme protein sequence has been successfully used to evolve thermostable enzymes (39,(42)(43)(44)(45)(46). The underlying assumption of this approach is that conserved amino acids can contribute to the enzyme stability under extreme conditions (36,43,(46)(47)(48).…”
mentioning
confidence: 99%
“…Of the rational design methods, a structureguided consensus approach combines information about the quaternary structure with knowledge of a few sequences that have moderate identity to reduce the number of target residues in a given protein to be mutated. At present, it is considered an effi-cient and reliable method for improving enzymatic properties (16,(22)(23)(24)(25).…”
mentioning
confidence: 99%